Dexrazoxane Protects Cardiomyocyte from Doxorubicin-Induced Apoptosis by Modulating miR-17-5p. (2nd March 2020) - Yu, Xiaoxue; Ruan, Yang; Shen, Tao; Qiu, Quan; Yan, Mingjing; Sun, Shenghui; Dou, Lin; Huang, Xiuqing; Wang, Que; Zhang, Xiyue; Man, Yong; Tang, Weiqing; et al.
Abstract : The usage of doxorubicin is hampered by its life-threatening cardiotoxicity in clinical practice. Dexrazoxane is the only cardioprotective medicine approved by the FDA for preventing doxorubicin-induced cardiac toxicity. Nevertheless, the mechanism of dexrazoxane is incompletely understood. The aim of our study is to investigate the possible molecular mechanism of dexrazoxane against doxorubicin-induced cardiotoxicity. We established a doxorubicin-induced mouse and cardiomyocyte injury model. Male C57BL/6J mice were randomly distributed into a control group (Con), a doxorubicin treatment group (DOX), a doxorubicin plus dexrazoxane treatment group (DOX+DEX), and a dexrazoxane treatment group (DEX). Echocardiography and histology analyses were performed to evaluate heart function and structure. DNA laddering, qRT-PCR, and Western blot were performed on DOX-treated cardiomyocytes with/without DEX treatment in vitro. Cardiomyocytes were then transfected with miR-17-5p mimics or inhibitors in order to analyze its downstream target. Our results demonstrated that dexrazoxane has a potent effect on preventing cardiac injury induced by doxorubicin in vivo and in vitro by reducing cardiomyocyte apoptosis. MicroRNA plays an important role in cardiovascular diseases. Our data revealed that dexrazoxane could upregulate the expression of miR-17-5p, which plays a cytoprotective role in response to hypoxia by regulating cell apoptosis. Furthermore, the miRNA and protein analysis revealed that miR-17-5p significantly attenuated phosphatase and tensin homolog (PTEN) expression in cardiomyocytes exposed to doxorubicin. Taken together, dexrazoxane might exert a cardioprotective effect against doxorubicin-induced cardiomyocyte apoptosis by regulating the expression of miR-17-5p/PTEN cascade.